2012
DOI: 10.1002/pca.2358
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Macrocyclic Ellagitannin Oenothein B in Plant Materials by HPLC‐DAD‐MS: Method Development and Validation

Abstract: The first HPLC method for quantification of OeB in plant materials was developed and validated. We also for the first time optimised the extraction conditions for OeB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 15 publications
(15 reference statements)
5
41
0
Order By: Relevance
“…Figure 1 shows chromatograms of the extract acquired at 254 and 350 nm, and Table 1 presents the UV-Vis and MS data of the detected compounds. A previous HPLC study showed that macrocyclic ellagitannin is the dominant constituent in C. lutetiana herb, forming 27.64% of the dry material (Granica et al, 2012). The present study confirmed this: total tannin content in the extract was 30.94±0.81% and total polyphenol content was 35.08±1.81%; this means that other phenolics such as flavonoids or phenolic acids are minor constituents, amounting to ~4%.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Figure 1 shows chromatograms of the extract acquired at 254 and 350 nm, and Table 1 presents the UV-Vis and MS data of the detected compounds. A previous HPLC study showed that macrocyclic ellagitannin is the dominant constituent in C. lutetiana herb, forming 27.64% of the dry material (Granica et al, 2012). The present study confirmed this: total tannin content in the extract was 30.94±0.81% and total polyphenol content was 35.08±1.81%; this means that other phenolics such as flavonoids or phenolic acids are minor constituents, amounting to ~4%.…”
Section: Resultssupporting
confidence: 77%
“…The herb of Circaea contains other constituents besides flavonoids, such as galloyl-and octylglucose derivatives as well as icariside B 2 (rare caprylic alcohol) (Kim and Kingston, 1996). Recent work of ours has shown the aerial parts of Circaea lutetiana to be a rich source of the macrocyclic ellagitannin oenothein B, which is characteristic for the whole Oenotheraceae family, and that the main flavonoid compounds in this plant material consist of glycosides of apigenin, among which some rare C,O-glycosides occur in high quantities (Granica et al, 2012;Granica and Kiss, 2013). The presence of ellagic acid derivatives as well as ellagic acid itself has also been confirmed in C. lutetiana (Granica and Kiss, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…hairy willowherb (Epilobium hirsutum), broad-leaved willowherb (Epilobium montanum) and rosebay willowherb (Epilobium angustifolium) had high ET content (>90 mg g À1 of the crude extract) and the main ET was macrocyclic dimer oenothein B (50) (Granica et al, 2012;Okuda et al, 1993) that covered 30-40% of the total peak area of the crude extracts. The content of other oligomeric compounds was also high (16-24% depending on the species).…”
Section: Orders Myrtales and Geranialesmentioning
confidence: 99%
“…We tested the three most popular species from the Epilobium genus: E. angustifolium L., E. parviflorum Schreb. and E. hirsutum L., standardized on oenothein B, as this is known to be the dominating compound . All extracts were characterized using the high‐performance liquid chromatography−diode array detector coupled with mass spectrometry (HPLC‐DAD‐MS/MS) method.…”
Section: Introductionmentioning
confidence: 99%